COMPARATIVE EVALUATION OF PAP SMEAR WITH HISTOPATHOLOGY IN CERVICAL LESION ACCORDING TO THE 2014 BETHESDA SYSTEM: AN INSTITUTIONAL STUDY - GOURANGA CHARAN PRUSTY; RANJAN KUMAR MALLICK; GOUTAMI DAS NAYAK; SUNANDA NAYAK; CHANDRAPRAVA MISHRA; TAPAS RANJAN MISHRA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objective of this study is to evaluate the efficacy of a pap smear using The 2014 Bethesda System (TBS) for the diagnosis of premalignant and malignant lesions of the uterine cervix. Methods: A prospective study was conducted in the Department of Pathology at the institution from November 2015 to October 2017. Fifty patients with an unhealthy cervix have undergone conventional Pap smears and histopathological biopsies with the suspicion of cervical malignancy or premalignancy attending the Obstetrics and Gynecology Outpatient Department. The obtained smears were arranged according to TBS. The tissue biopsies have been processed routinely and they are stained with hematoxylin and eosin for histopathological diagnosis. Furthermore, cases such as non-neoplastic, metastatic lesions, and recurrent cases were excluded from this study. Results: The common age group has been identified as between 41 and 60 years and patients had low educational levels. Sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy observed in this study were 89.28%, 63.63%, 64.1%, 72.72%, and 72% respectively. Conclusion: Pap smear is a simple, effective, inexpensive procedure that can be routinely used as a screening tool for screening cervical cancer. TBSs also provide a standard approach for cytological evaluation that helps in the early detection of premalignant and malignant cervical lesions.